The readiness of pedagogical personnel to realize the inclusive education in general educational institution - Kondrova, Aija; Orska, Rita; Rozenfelde, Mārīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The dilemma between general pedagogical offer and individual needs of every student has been topical in all ages and now, too. An inclusive education now has been considered a new hope and a possible solution for the pedagogical dilemma – how to provide educational and development necessities of every child at comprehensive school. Teacher is a crucially essential person in the practice of inclusive education. The teachers mostly have to be professionally competent in order to reveal varied necessities, individual academic achievements, the social and culture environment, where these students live, of every student; and it provides an opportunity to find out how to facilitate academic achievements of every student most efficiently. The research reveals the work conditions of Latgale region teachers through the implementation of inclusive education at educational institutions of different level.